Machine-learning-based earthquake locations reveal the seismogenesis of the 2020 Mw 5.0 Qiaojia, Yunnan earthquake. Issue 3 (18th October 2021) - Zhou, Lianqing; Zhao, Cuiping; Zhang, Miao; Xu, Lisheng; Cui, Rensheng; Zhao, Ce; Duan, Mengqiao; Luo, Jun
SUMMARY: A moment magnitude ( M w ) 5.0 earthquake hit Qiaojia, Yunnan, China on 18 May 2020. Its hypocentre is only approximately 20 km away from the Baihetan reservoir, the second largest hydropower station in China. The Baihetan Reservoir is located at the junction of multiple fault zones on the eastern boundary of the Sichuan-Yunnan rhombic block, an area with high background seismic activity. The Baihetan Reservoir was planned to be impounded in April 2021 and the M w 5.0 earthquake occurred during its water-retaining. Thus, it is critical to investigate the seismogenesis of the Qiaojia M w 5.0 main shock and evaluate the risk of inducing earthquakes near the Baihetan Reservoir after impoundment. In this study, we built a complete and accurate earthquake catalogue to analyse seismicity in the reservoir area before and after the M w 5.0 Qiaojia earthquake. We adopted a machine learning-based seismic phase picker, PhaseNet, to automatically detect seismic picks from continuous raw seismic data. Seismic phase picks were associated and located using sequential earthquake association and location methods, including REAL, VELEST and hypoDD. We eventually obtained high-precision locations of 1640 earthquakes by the hypoDD. The distribution of earthquake locations indicates that a concealed fault nearly vertical to the surface accommodated the M w 5.0 Qiaojia main shock. The majority of its aftershocks is located within a narrow depth range of 8–13 km, indicating that the stresses in the hypocentral area were concentrated near the hypocentre of the M w 5.0 earthquake. Along with focal mechanism solutions, we suggested that the M w 5.0 Qiaojia earthquake is more likely a tectonic earthquake. However, we cannot exclude the possibility that earthquakes could be induced after the impoundment of Baihetan Reservoir, because the identified concealed fault is located in the middle of many large fault zones and only 20 km away from the Baihetan Reservoir.